KENDALA YANG DIHADAPI DALAM PELAKSANAAN TUGAS HAKIM PENGAWAS DAN PENGAMAT DALAM PEMBINAAN NARAPIDANA KELAS II A SAMARINDA - Fauzi Halim (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT Judge accomplish their supervisors and observers in the monitoring and observation duties in connection with the execution of the decision of the judge by the prosecutor as executor is not done in an absolute and immediate. Supervision is not done directly and absolutely caused by the prosecutor and the judge are structurally different, in this case the prosecutor remains responsible to his superiors that the Head of the State Attorney. In his charge, the prosecutor as executor will prepare minutes of execution of court decisions which will then be submitted to the Chief State Prosecutor. Supervision of other equally important to be done by supervisors and observers judge is to convict on parole. During the conditional does not undergo criminal convict in prisons, the convict can move freely in the community. The role of the supervisory judges and observers will be necessary here to monitor the behavior of the convict on parole. Supervision and observation by supervisors and observers judge of prisoners who have completed their criminal and parole of prisoners as required by the Supreme Court Circular No. 7 of 1985 on Implementation Guidelines Task Supervisory Judge and Observer done by supervisors and observers judge cooperated with authorities village governments, schools, foundations working in the social field that was used to help the development of the former prisoners, such as BISPA hall, the Directorate-General of Social Rehabilitation Rehabilitation and social Affairs social waiter, etc. Some of the obstacles encountered in carrying out the duties of judges supervisors and observers are: The lack of clear sanctions for the prosecution when the judge did accost for the delay in execution of court decisions, resulting in the discharge of the prosecutor as executor of the supervisory role of the judge and the observer is not very meaningful; Not tied suggestion supervisory judge and observer in the form of improved types of training provided to the inmates. Forms and coaching and mentoring program that will be given to prisoners is basically composed by prisons chief, the head of programming prisons can receive advice from supervisors and observers judge or observer team Corrections. This makes the suggestion of the judge is not binding on the controller and observer chief prisons; A sense of the prisons that they are more aware of how the development of convicts because they have seen and mingle with inmates every day. Thus they feel better knowing what is best the needs of the inmates. Difficult to judge supervisors and observers visit more regularly to the prisons because the judge has the task to another in the District Court as a judge hearing the case filed in the State Court